PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP FINANCIAL PERFORMANCE MELALUI EMPLOYEE SATISFACTION SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN DI SURABAYA - Oey Novita Wijaya (Business Accounting Review, 2015)
This study aimed to examine the affect of transformational leadership on financial performance with employee’s satisfaction as intervening variable. The samples and data used in this study were obtained from 300 employees in 35 banking companies in Surabaya by using questionnaire and banking company’s financial statements of 2011-2013. The method of data processing was done by using descriptive analysis and partial least square method (PLS).The result showed that transformational leadership gave positive and significant influence on employee satisfaction; transformational leadership gave positive and significant influence on the financial performance; employee satisfaction gave positive and significant influence on the financial perfomance, and there was no direct influence of transformational leadership on the financial performance through employee satisfaction as the intervening variable.